2016
DOI: 10.1128/jb.01010-15
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Dual Functions of Bacterial Enhancer-Binding Protein Rrp2 of Borrelia burgdorferi

Abstract: It is well established that the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…We and others showed that Rrp2 phosphorylation is required for cell growth, in addition to activation of σ 54 -σ S cascade (34,35). If HK2 overexpression reduces the level of Rrp2 phosphorylation, one would expect that it will affect spirochetal growth.…”
Section: Hk2 Functions As a Phosphatase Of Rrp2mentioning
confidence: 90%
“…We and others showed that Rrp2 phosphorylation is required for cell growth, in addition to activation of σ 54 -σ S cascade (34,35). If HK2 overexpression reduces the level of Rrp2 phosphorylation, one would expect that it will affect spirochetal growth.…”
Section: Hk2 Functions As a Phosphatase Of Rrp2mentioning
confidence: 90%
“…Compared with the other two structural domains (i.e., R and D), the central C domain is highly conserved among bEBPs (Studholme and Dixon, ; Rappas et al ., ; Wigneshweraraj et al ., ; Bush and Dixon, ). Moreover, previous studies have indicated that the G239 residue in Rrp2's C domain could readily be mutated in B. burgdorferi (Yang et al ., ; Boardman et al ., ; Ouyang et al ., ; Blevins et al ., ; Groshong et al ., ; Yin et al ., ). Of note, the residue G239 is located just upstream of the Walker B motif (positions 240‐245) in Rrp2's C domain (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, many structural and biochemical studies (Morett and Segovia, 1993;Osuna et al, 1997;Pelton et al, 1999;Ray et al, 2005;Sallai and Tucker, 2005;Rappas et al, 2006Rappas et al, , 2007Batchelor et al, 2008;Wigneshweraraj et al, 2008;Bush and Dixon, 2012) have indicated that nucleotide binding and hydrolysis cause significant conformational changes of bEBPs, which is directly linked to the activation of r 54 -dependent genes. Despite that Rrp2's D domain has been suggested to be dispensable for the activation of r 54dependent rpoS transcription (Burtnick et al, 2007;Blevins et al, 2009), one recent study reported that Rrp2's D domain, as well as its R domain, is required for spirochetal growth (Yin et al, 2016); Rrp2 variants with the D domain or R domain truncated were incapable of supporting borrelial growth in BSK medium. Our study here adds that Rrp2's ATPase activity also is required for borrelial viability and the regulation over r 54 /RpoS-independent essential genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations